Menyikapi Fenomena Flexing Berdasarkan Spiritualitas Keugaharian - Sondang Lubis (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
The purpose of this research is to understand that the current development of technology has brought about a phenomenon known as flexing. People who frequently show off their wealth, possessions, and achievements on social media are referred to as flexing. This study employs expert theories related to the spirituality of modesty, particularly A. Setyo Wibowo's theory, which emphasizes sophrosyne (moderation). Modesty teaches individuals to live sufficiently, without excess. The study uses a qualitative research method with a phenomenological approach. Data collection techniques include observation and in-depth interviews. The findings of this study suggest that the phenomenon of flexing should be addressed through the spirituality of modesty by practicing gratitude in all circumstances, learning self-control, and living with love. Thus, society and social media users are encouraged to always embrace the spirituality of modesty.